PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA ASN DENGAN KOMPENSASI SEBAGAI VARIABEL MODERATING PADA DINAS PERTANIAN DAN KETAHANAN PANGAN KABUPATEN SITUBONDO - Romadan, Egi Sambila; Ediyanto, Ediyanto; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2024)
The Situbondo Regency Agriculture and Food Security Service is a government agency that operates in the agriculture and food sector. In this way, the human resources involved can apply discipline in their work and are able to develop new innovations in the fields of agriculture and food. This research aims to analyze the influence of Work Discipline, Work Motivation and Compensation on ASN Performance in the Situbondo Regency Agriculture and Food Security Service. This research was conducted using a quantitative approach and sampling techniques determined by sampling quotas. Data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of hypothesis testing using the Smart PLS 3.0 application show that Work Discipline has a significant effect on Performance, Work Motivation has a significant effect on Performance. The results of hypothesis testing moderated by the Compensation variable show that the Work Discipline variable has a positive effect on performance but is not significant, the Work Motivation variable moderated by the Compensation variable shows a positive but not significant effect.